The Correlation Between Leg Muscle Strength, Balance, and Reaction Speed to the Ability of the Crescent Kick: Hubungan Kekuatan Otot Tungkai, Keseimbangan, dan Kecepatan Reaksi dalam Tendangan Sabit - Muhammad zainal Ikhwan; Wahyu Setia Kuscahyaning Putri; Nurman Ramadhan (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2026)
This study aims to determine the correlation between leg muscle strength, balance, and reaction speed to the ability of the sickle kick in pencak silat athletes Elementary School 1 Bangilan. The study used a correlational method with a quantitative approach. The population and sample in this study were all 20 students of the pencak silat extracurricular Elementary School 1 Bangilan with a saturated sampling technique. The research instruments included a leg muscle strength test using a vertical jump, a balance test using a standing stork test, a reaction speed test using a 10-meter run, and a 10-second sickle kick ability test. Data analysis was carried out using the Pearson Product Moment correlation test and multiple linear regression with the help of the SPSS 23 program. The results showed that partially balance had a significant relationship to the ability of the sickle kick (r = 0.54; p < 0.05), while leg muscle strength and reaction speed had a weak and insignificant relationship. Together, leg muscle strength, balance, and reaction speed had a significant relationship to the ability of the sickle kick with a multiple correlation coefficient (R) of 0.621 and a coefficient of determination (R²) of 0.386. This indicates that these three variables contribute 38.6% to the sickle kick's ability. It can be concluded that balance is the most dominant physical factor in supporting the sickle kick ability of pencak silat athletes.